Genes Associated With Psychrotolerant Bacillus cereus Group Isolates - Beno, Sarah M.; Orsi, Renato H.; Cheng, Rachel A.; Kent, David J.; Kovac, Jasna; Duncan, Diana R.; Martin, Nicole H.; Wiedmann, Martin (Frontiers in Microbiology, 2019)
The Bacillus cereus group comprises 18 different species, including human pathogens as well as psychrotolerant strains that are an important cause of fluid milk spoilage. To enhance our understanding of the genetic markers associated with psychrotolerance (defined here as > 1 log10 increase in cfu/mL after 21 days incubation at 6°C) among dairy-associated B. cereus group isolates, we used genetic (whole genome sequencing) and phenotypic methods (growth in Skim Milk Broth [SMB] and Brain Heart Infusion [BHI] broth) to characterize 23 genetically-distinct representative isolates from a collection of 503 dairy-associated isolates. Quality threshold clustering (QTC) identified 3 categories of psychrotolerance: (i) 14 isolates that were not psychrotolerant in BHI or SMB, (ii) 6 isolates that were psychrotolerant in BHI but not in SMB, and (iii) 2 isolates that were psychrotolerant in BHI and SMB. One isolate, which was psychrotolerant in BHI broth but was just below the cut-off of > 1 log10 cfu/mL increase in SMB was not assigned to a cluster. A maximum likelihood phylogeny constructed with core genome single nucleotide polymorphisms (SNPs) classified all psychrotolerant isolates (i.e., psychrotolerant in BHI) into clade VI (representing B. mycoides/weihenstephanensis). Analysis of correlations between gene ortholog presence or absence patterns and psychrotolerance identified 206 orthologous gene clusters that were significantly overrepresented among psychrotolerant strains, including 2 clusters of cold shock proteins, which were identified in 8/9 and 7/9 psychrotolerant isolates. Gene ontology analyses revealed 36 gene ontology terms that were overrepresented in psychrotolerant isolates, including putrescine catabolic processes and putrescine transmembrane transporter activity. Lastly, Hidden Markov Model searches identified 3 protein family motifs, including cold shock domain proteins and fatty acid hydroxylases that were significantly associated with psychrotolerance in BHI broth. Analyses of CspA sequences revealed a positive association between psychrotolerant strains and a previously identified “psychrotolerant” CspA sequence. Overall, our data highlight genetic and phenotypic differences in psychrotolerance among B. cereus group dairy-associated isolates and show that psychrotolerance is dependent on the growth medium. We also identified a number of gene targets that could be used for specific detection or control of psychrotolerant B. cereus group isolates.